Last bookstore on Earth - Braun-Arnold, Lily (New York Delacorte Press, 2025)
In a dystopian world devastated by The Storm, seventeen-year-old Liz finds refuge in her old bookstore, but when Maeve breaks in seeking shelter from another impending storm, the two confront their secrets and inner demons as they fight for their lives.
Ages 12 and up.
Grades 10-12.
115451
Keywords: End of the world -- Fiction; Survival -- Fiction; Lesbians -- Fiction; Young adult fiction; Young adult fiction -- Science Fiction -- Apocalyptic & Post-Apocalyptic.; Young adult fiction -- Girls & Women; Young adult fiction -- Romance -- LGBTQ+; LGBTQ; LGBT Fiction -- LGBTQ -- Dystopian -- Young adult romance -- Romantic Novels; Young adult fiction; Romance fiction; Novels; Romans